Analysis Of The Influence Of International Prices, Exchange Rates, Export - Import Quotas, Tariff And Non-Tariff Policies On The Volume Of Indonesian Palm Oil (CPO) Exports To India - Mrs. Rashika fauzi; Renny Oktafia (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to analyze the influence of international prices, exchange rates, export-import quotas, as well as tariff and non-tariff policies on the volume of Indonesian palm oil (CPO) exports to India. Using secondary data covering the period 1993 – 2023. Analysis was carried out using the ECM, OLS and Classical Assumption Test methods. The research results show that international prices have a positive and significant influence and the exchange rate has a weaker and insignificant positive relationship on the volume of Indonesian CPO exports to India. Export - import quotas have a weak and insignificant relationship and tariff and non-tariff policies have a positive and significant influence on the volume of Indonesian CPO exports to India. This research is expected to provide insight for policy makers and industry players in formulating appropriate strategies to increase the competitiveness of Indonesian CPO exports to the Indian market.